Does Co-Occurring Anxiety Modulate ADHD-Related Cognitive and Neurophysiological Impairments?. Issue 8 (June 2021) - Adamo, Nicoletta; Michelini, Giorgia; Cheung, Celeste H. M.; Buitelaar, Jan K.; Asherson, Philip; Rijsdijk, Fruhling; Kuntsi, Jonna
Objective: This study investigates whether anxiety modulates cognitive-performance, electrophysiological and electrodermal processes that we previously found impaired in individuals with ADHD.Method: Self-reported anxiety symptoms, cognitive-electrophysiological measures of response inhibition, working memory, attention, conflict monitoring, error processing, and peripheral arousal during three cognitive tasks were obtained from 87 adolescents and young adults with ADHD and 169 controls. We tested the association of anxiety symptoms with each measure and whether controlling for anxiety symptoms attenuates the ADHD–control difference for each measure.Results: Individuals with ADHD showed significantly elevated anxiety symptoms compared with controls. Only commission errors on a Continuous Performance Test (measuring response inhibition) were significantly associated with anxiety symptoms and only among controls, with the ADHD–control difference in this measure remaining significant.Conclusion: Using a wide range of cognitive, electrophysiological, and electrodermal measures, our investigation suggests, overall, limited malleability of these impairments in individuals with ADHD irrespective of their levels of anxiety.